1693 Mass. Acts 48, An Act for Regulating of the Militia, ch. 3, §§ 1, 5 - (:unkn) unknown (General Publisher, 1693)
. That all male persons from sixteen years of age to sixty, (other than such as are herein after excepted), shall bear arms, and duly attend all musters and military exercises of the respective troops and companies where they are listed . . . § 5 That every listed solider and other householder (except troopers) shall be always provided with a well fixed firelock musket, or musket or bastard musket bore . . .
--
Keywords: ARMED FORCES